PENDAMPINGAN ADMINISTRASI PENGAJUAN LEGALITAS SD MUHAMMADIYAH 4 KOTA BATU - Aviani Widyastuti; Ahmad Waluya Jati; Ike Arisanti (Universitas Muhammadiyah Malang, 2020)
This community service activity aims to assist in the improvement and control of legality administration in one of the Muhammadiyah Business Charities (AUM) in Batu City, namelySD Muhammadiyah 4. The administration improvement and control referred to in this case is related to the maintenance of AUM establishment permits that are aligned with the status ofAUM legal entity namely Business Identification Number (NIB) and uniformity of Taxpayer Identification Number (NPWP). This activity will be carried out in three stages, namely the NIBmanagement stage, the financial reporting and taxation stage and the AUM governance stage. However, in this service activity it was proposed as a form of solving the problems of SD Muhammadiyah 4 Kota Batu for the first stage, namely the management of NIB. Problem solving in the first phase of this activity is to use the methods of presentation, training and assistance as well as dialogue. The outputs of the devotion activities in this first stage are SD Muhammadiyah Kota Batu can arrange and complete licensing administration procedures related to NIB and uniformity of NPWP.